2014
DOI: 10.7554/elife.04551
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Na+ spikes enable cortical input to drive action potential output from hippocampal CA2 pyramidal neurons

Abstract: Synaptic inputs from different brain areas are often targeted to distinct regions of neuronal dendritic arbors. Inputs to proximal dendrites usually produce large somatic EPSPs that efficiently trigger action potential (AP) output, whereas inputs to distal dendrites are greatly attenuated and may largely modulate AP output. In contrast to most other cortical and hippocampal neurons, hippocampal CA2 pyramidal neurons show unusually strong excitation by their distal dendritic inputs from entorhinal cortex (EC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
64
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 63 publications
(118 reference statements)
9
64
2
Order By: Relevance
“…We filled the neurons with biocytin during whole-cell recordings, performed morphological reconstructions using Neurolucida, and conducted morphometric analyses. Some of the data from CA1 and CA2 PNs presented here have been reported in our previous paper (Sun et al, 2014). We found CA3c has the shortest total dendritic length across the subregions (Figure S1A,B).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…We filled the neurons with biocytin during whole-cell recordings, performed morphological reconstructions using Neurolucida, and conducted morphometric analyses. Some of the data from CA1 and CA2 PNs presented here have been reported in our previous paper (Sun et al, 2014). We found CA3c has the shortest total dendritic length across the subregions (Figure S1A,B).…”
Section: Resultsmentioning
confidence: 77%
“…We previously found that CA2 receives a much greater excitatory drive from PP inputs than does CA1 or CA3 (Chevaleyre and Siegelbaum, 2010; Srinivas et al, 2017; Sun et al, 2014). Here we examined the heterogeneity of direct cortical excitation of CA3 across the transverse axis.…”
Section: Resultsmentioning
confidence: 97%
“…Under the conditions of our experiments, the monosynaptic IPSP evoked by SLM stimulation, determined in separate experiments with glutamatergic transmission blocked (50 μm APV and 10 μm CNQX), was very small, less than 10% the size of the inferred IPSP evoked with excitatory transmission intact (Figure S2; at 80V, the sPN IPSP = 0.06±0.06mV and the dPN IPSP = 0.11±0.02mV; n=7, p=0.25 by two-way ANOVA). Moreover, feedback inhibition is unlikely to contribute to the net IPSP because the peak PP-evoked PSP evoked with inhibition intact is extremely small (<1 mV), and thus fails to evoke CA1 action potential output (as evidenced by the failure of SLM stimulation to evoke a detectable population spike in the CA1 PN cell layer; Chevaleyre and Siegelbaum, 2010; Sun et al, 2014). …”
Section: Resultsmentioning
confidence: 99%
“…Another notable anatomical feature of CA2 pyramidal neurons is that, in the mouse, their apical dendrites are branched in a way that may be particularly well suited for transmitting signals from the distal synapses in the stratum lacunosum-moleculare (SLM) to cell bodies 54,56,57 . These distal synapses arising from layer II of the entorhinal cortex onto CA2 pyramidal neurons would therefore be more effective at initiating firing of the postsynaptic pyramidal neurons than those synapses from layer III in the SLM of the mouse CA1 (REF.…”
Section: Properties Of Ca2 Neuronsmentioning
confidence: 99%
“…CA2 pyramidal neurons also demonstrate prominent dendritic sodium spikes 57 . It has been hypothesized that dendritic sodium spikes, in conjunction with particular branching patterns of the apical dendrites, provide a mechanism by which distal inputs from the entorhinal cortex layer II can be effectively transmitted to the cell body and cause CA2 pyramidal neurons to fire.…”
Section: Properties Of Ca2 Neuronsmentioning
confidence: 99%